Health priorities: Strategies to reduce maternal mortality in the San Martín region - Sánchez-Dávila, Keller (2021)
Introduction: The formulation of a public policy must be aligned to the needs of the citizenry, where the intervention must be articulated with the different actors and levels of government to ensure the fulfillment of the objectives. The implementation of public policies in health has a great connotation, where the priority is the health of the population based on the dimensions of distributive justice and the maximization of health. Therefore, it is necessary to identify three basic elements: maximizing health, reducing inequalities and access; always preserving the standards of care and ensuring the optimal performance of health providers. Faced with the above, the following question arises: What is the influence of regional health priorities on maternal mortality in the San Martín Region? With the objective of determining the influence of regional health priorities on maternal mortality in the San Martín Region. Likewise, identify the level of formulation of regional health priorities in maternal mortality in the San Martín Region. Identify the level of implementation of regional health priorities in maternal mortality in the San Martín Region. Identify the level of participation of the actors involved in regional health priorities in maternal mortality in the San Martín Region. Identify the budget level assigned in the regional health priorities for maternal mortality in the San Martín Region. Objective: To determine the influence of regional health priorities on maternal mortality in the San Martín Region. Materials and Methods: The research was non-experimental, with a correlational descriptive study design. The sample consisted of 20 officials, the instrument used was the questionnaire and the data collection form. Results: Among the results of the study, the level of formulation of regional health priorities stands out with an "Inadequate" level with 50%, the implementation of regional health priorities shows an "Inadequate" level with 50%, the participation of Stakeholders show an “Inadequate” level with 65% and the budget allocated for health priorities reaches an “Inadequate” level with 45%. Conclusions: There is a Pearson correlation coefficient of (-0.634) indicating that there is an inversely proportional mean correlation between the regional health priority variables with maternal mortality in the San Martín Region; However, it should be noted that there is a 40% influence on the decrease in maternal death (negative relationship) as a result of regional priorities. Likewise, elements studied such as the formulation, implementation, involvement of actors and the budget assigned to regional health priorities are inadequate, affecting the fulfillment of maternal health indicators.